Nitrofurantoin associated pulmonary fibrosis - Ogundipe, Olayinka A. (International Journal of Basic & Clinical Pharmacology, 2020)
This report describes the case of an 83 years old woman presenting to hospital due to a fall, and acute confusion. On admission, she was diagnosed as having clinical and plain X-ray features of a pneumonia. Following treatment and recovery from the pneumonia, she was noted to have persistent clinical signs of bilateral lung crackles on auscultation. A high-resolution computerised tomography scan showed signs of interstitial lung disease consistent with pulmonary fibrosis. Of relevance was a medication history that indicated oral nitrofurantoin had been initiated in primary care for the long-term prophylaxis of recurrent urinary tract infections. Given the prolonged duration of use of ten years, we considered the possibility of this being an adverse drug reaction in the form of nitrofurantoin associated pulmonary fibrosis. This report also briefly reviews the relevant literature on nitrofurantoin associated pulmonary fibrosis and to promote objectivity in the pharmacovigilance related reporting. The report has been reviewed with the aid of two validated causality assessment systems.